PENGARUH PERSEPSI DALAM SISTEM PERPAJAKAN, DISKRIMINASI PAJAK, KEADILAN PAJAK, DAN TAX KNOWLEDGE TERHADAP TAX EVASION - Rizmanda Masita Murbiyanti; Fatchur Rochman (Universitas Merdeka Madiun, 2025)
This study aims to examine the influence of Taxation Systems, Tax Discrimination, Tax Justice, and Tax Knowledge on Tax Evasion. Technique in taking sample use purposive sampling method to Individual Taxpayers Registered in KPP Pratama Madiun Fiscal Year 2018. Data obtained from the primary data whish is use the questionnaire method. Data analysis was done with a doble linier regression with SPSS program version 25 for windows. The results showed that the Taxation Systems and Tax Discrimination variable has no significantly affect on ethical behavior of Tax Evasion. While the Tax Justice and Tax Knowledge variable has significantly affect on ethical behavior of Tax Evasion.